A Near‐Infrared Dye That Undergoes Multiple Interconversions through Acid–Base Equilibrium and Reversible Redox Processes. Issue 24 (9th May 2017) - Asai, Kengo; Fukazawa, Aiko; Yamaguchi, Shigehiro
Abstract: A near‐infrared (NIR) polymethine dye (1 ), consisting of a cyclohepta[1, 2‐ b ;4, 3‐ b′ ]dithiophene and two phenol moieties, was synthesized. This dye exhibited pH‐responsive changes in its photophysical properties due to a two‐step acid–base equilibrium that produced a protonated cation (1H + ) and an anion (1 − ). While1H + showed an intense fluorescence in the red region of the visible spectrum, 1 − exhibited a strong absorption in the NIR region. The tropylium ion character in1H + induces high p K a1 and p K a2 values for1 . Moreover, a stable radical (1 . ) was prepared, which showed a NIR absorption band with a maximum at circa 1600 nm. The cyclic voltammogram of1 . revealed a two‐step reversible redox process that produced1 − and the cation1 +, which is different from1H + . These redox processes accompany drastic electrochromic changes in the vis–NIR region. Overall, 1 is susceptible to multiple interconversions between five forms, due to the multifaceted character of the cycloheptadithiophene skeleton. Abstract : Kaleidoscopic : A cyclohepta[1, 2‐ b ;4, 3‐ b′ ]dithiophene bearing two phenol terminal groups shows interconversions among five forms, including its protonated, neutral, and anionic species as well as its cationic and radical species with drastic changes in the absorption and emission properties in the visible to near‐IR region. The central seven‐membered ring plays crucial roles in mediating these multiple changes.